Maqashid al-Syari’ah al-Syatibi: In The Paradigm Muslim Society as Methodology of Zakat Law - Ikhwanuddin Harahap; Mohd Syahiran Abdul Latif; Nispul Khoiri (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2022)
This research is collaborative research of library research and field research. Using a qualitative method with a normative legal approach, namely Islamic law (usul fiqh) and naturalistic phenomena. Research exploring the existence of Regional Regulations (Perda) on Zakat Management in Medan City is a necessity, to explore the potential for greater zakat, but the Perda in question has not yet been legislated. The many inhibiting factors, two factors need attention in this study, namely: First, the paradigm of the Muslim community in the city of Medan towards the Syafii fiqh legal methodology is since the majority of Muslims are based on the Syafii fiqh school, thus denying other legal methodologies such as Maqashid al-Syariah which are quite relevant to strengthening the zakat regulation. Second, the paradigm of the Muslim community in the city of Medan has not seen the urgency of Maqashid al-Syariahal-Syatibi as an element of strengthening the regional regulation on zakat in Medan City. The results of the study show that: First, the Muslim community of Medan city does not yet know and fully understand Maqashid al-Syariah al-Syatibi as a legal methodology, because of the strong and strong Syafii school of jurisprudence as a single majority school. Second, Maqashid al-Syariah al-Syatibi is urgent as a solution to strengthening the regional regulation on zakat in the city of Medan with the substance of high benefit aspects, starting from the position of regulation, management to positive benefits for the Muslim community in the city of Medan